Analisis Pelaksanaan Program Istithaah Kesehatan Jemaah Haji Berdasarkan Permenkes Nomor 15 Tahun 2016 (Studi Kasus di Puskesmas Tigo Baleh Kota Bukittinggi) - Shonia Ramayany; Ariyun Anisah (Lembaga Yasin AlSys, 2026)
Hajj is an obligation for Muslims who are able to perform it, including in terms of health or health istithaah. The government issued Peraturan Menteri Kesehatan Nomor 15 Tahun 2016 tentang Istithaah Kesehatan Jemaah Haji as a guideline for examining, developing, and determining the health status of Hajj pilgrims. This study aimed to describe the implementation of the Hajj pilgrims’ health istithaah program based on Peraturan Menteri Kesehatan Nomor 15 Tahun 2016 at the Tigo Baleh Community Health Center, Bukittinggi City. The study employed a qualitative approach with a descriptive method and a case study design. Data were collected through interviews, observations, and documentation involving informants from the Bukittinggi City Health Office, the Tigo Baleh Community Health Center, and Hajj pilgrims. The results showed that the program’s implementation generally complied with the applicable provisions, including phased health examinations, health development, determination of istithaah status, recording and reporting, and the provision of human resources and supporting facilities and infrastructure. The program’s implementation was also adjusted to Keputusan Menteri Kesehatan Nomor HK.01.07/MENKES/2118/2023 by incorporating urine examinations for women of reproductive age and screening for dementia and cognitive function. This study concludes that the Hajj pilgrims’ health istithaah program at the Tigo Baleh Community Health Center has been implemented comprehensively and in an integrated manner. These findings provide practical implications regarding the need to strengthen continuous health development, improve personnel competence, optimize information systems, and enhance cross-sectoral coordination to improve the health preparedness of Hajj pilgrims.